Proteomics and network pharmacology of Ganshu Nuodan capsules in the prevention of alcoholic liver disease - Yang, Xiaonan; Wang, Lei; Cui, Xuejie; Zhang, Jing; Liang, Ying; Luo, Zhaojing; Zhou, Bingxue; Jiang, Zheng; Yang, Rachel Y. H.; Wu, Yi; Wei, Kunhua; Du, Maobo; et al. (Frontiers in Endocrinology, 2023)
Introduction: Ganshu Nuodan is a liver-protecting dietary supplement composed of Ganoderma lucidum (G. lucidum) spore powder, Pueraria montana (Lour.) Merr. (P. montana), Salvia miltiorrhiza Bunge (S. miltiorrhiza) and Astragalus membranaceus (Fisch.) Bunge. (A. membranaceus). However, its pharmacodynamic material basis and mechanism of action remain unknown. Methods: A mouse model of acute alcohol liver disease (ALD) induced by intragastric administration of 50 % alcohol was used to evaluate the hepatoprotective effect of Ganshu Nuodan. The chemical constituents of Ganshu Nuodan were comprehensively identified by UPLC-QTOF/MS, and then its This is a provisional file, not the final typeset article pharmacodynamic material basis and potential mechanism of action were explored by proteomics and network pharmacology. Results: Ganshu Nuodan could ameliorate acute ALD, which is mainly manifested in the significant reduction of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in serum and malondialdehyde (MDA) content in liver and the remarkably increase of glutathione (GSH) content and superoxide dismutase (SOD) activity in liver. Totally 76 chemical constituents were identified from Ganshu Nuodan by UPLC-QTOF/ MS, including 21 quinones, 18 flavonoids, 11 organic acids, 7 terpenoids, 5 ketones, 4 sterols, 3 coumarins and 7 others. Three key signaling pathways were identified via proteomics studies, namely Arachidonic acid metabolism, Retinol metabolism, and HIF-1 signaling pathway respectively. Combined with network pharmacology and molecular docking, six key targets were subsequently obtained, including Ephx2, Lta4h, Map2k1, Stat3, Mtor and Dgat1. Finally, these six key targets and their related components were verified by molecular docking, which could explain the material basis of the hepatoprotective effect of Ganshu Nuodan. Comclusion: Ganshu Nuodan can protect acute alcohol-induced liver injury in mice by inhibiting oxidative stress, lipid accumulation and apoptosis. Our study provides a scientific basis for the hepatoprotective effect of Ganshu Nuodan. in acute ALD mice and supports its traditional application.